Cigarette Smoking in Filipino Sexual-Minority Men: Further Evidence of Disparities in the Philippines - Manalastas, Eric Julian; Cabrera, Nicolo L. (Silliman Journal, 2022)
Empirical studies in lesbian, gay, bisexual, and transgender (LGBT) health have documented significant disparities in risk behaviors and health outcomes across sexual orientation and gender identity. One such disparity lies in tobacco use. Surveys based on representative samples (Jabson, Farmer, & Bowen, 2014; Manalastas, 2012; Tang et al., 2004) as well as meta-analyses (Lee, Griffin & Melvin, 2009; Marshal et al., 2008) indicate that gender and sexual minorities generally have disproportionately higher rates of smoking than heterosexuals. This paper builds on previous research in the Philippines that presented initial evidence for cigarette smoking disparities among sexual-minority youth (Manalastas, 2012). We examine this issue again using a different nationally representative sample of Filipino men. Analysis of archival data from the National Demographic and Health Survey showed evidence for disparities in tobacco use based on sexual-minority status. Current smoking was disproportionately higher among sexual-minority men (67%) than heterosexual men (54%). Filipino sexual-minority men also began smoking significantly earlier—about a year—than heterosexual men. No differences in smoking volume was found—both sexual-minority and heterosexual Filipino male smokers smoked an average of 10-11 sticks a day. The findings point to one important disparity in Filipino LGBT health risks: the need to address the disproportionately higher uptake of tobacco use, one of the leading preventable causes of morbidity and mortality in the world, among sexual-minority Filipino men.